What is the Ethics of Faith? - K. Shcotkina (Українське Pелігієзнавство, 2005)
An inexperienced law-abiding citizen, far from the intricacies of church-state relations, the turmoil surrounding the newly devised Ethics of Faith course and the firm intention of the Ministry of Education and Science to develop and introduce this course from September 1 this year should surprise. "Where to rush into such a heat"? What is the Ethics of Faith? And, most importantly, democratic or undemocratic? Is it advisable or inappropriate? After all, it would seem simpler - let everyone play in their own territory: the school - gives knowledge, the family - deals with the upbringing of the child and decides whether to be religious or not, the church educates the children entrusted to them by the family, appropriate values ​​and outlook.